Tanggung Jawab Notaris/PPAT terhadap Akta yang Dibatalkan oleh Pengadilan - Lidya Christina Wardhani (Lex Renaissance, 2017)
AbstractNotary / PPAT as one public official has an important role in guaranteeing the rule of law, order and legal protection through an authentic deed made by and before him, the authentic act is strong evidence and if there is a dispute in court unless it could be proved guilty , so the deed of Notary / PPAT provide a perfect proof. The problem is how responsibility Notary / PPAT of the certificate canceled by the court? how the legal consequences of the Notary / PPAT due to the cancellation of an authentic act by a court ?. This study is a normative research with the approach of legislation, analytical approach and the approach to the case. The results showed first, Shape responsibility Notary / PPAT of the certificate canceled by the Court related to the case in this study included, civil liability, criminal and administrative. Second, Good cancellations due to civil, criminal, or administrative error by the Notary / PPAT in deed, in general due to the cancellation of the law by the Court of the authentic act is null and void, irrevocable and degraded the strength of evidence.Keywords: Notary, Responsibility, Deed, the Court